2011
DOI: 10.1029/2011gl048532
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the impact of aerosols at northern and southern midlatitudes on heterogeneous ice formation

Abstract: Three cloud data sets, each covering four months of observations, were recently recorded with a lidar at Punta Arenas (53°S), Chile, at Stellenbosch (34°S, near Cape Town), South Africa, and aboard the research vessel Polarstern during three north‐south cruises. By comparing these observations with an 11–year cloud data set measured with a lidar at Leipzig (51°N), Germany, the occurrence of heterogeneous ice formation (as a function of cloud top temperature) for very different aerosol conditions in the norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(208 citation statements)
references
References 18 publications
11
195
2
Order By: Relevance
“…Lidars are used since the 1970s to monitor clouds and their evolution, although primarily cirrus and mixed-phase clouds (Platt, 1973(Platt, , 1977Sassen, 1991). Our group also contributed to these observations over the last 25 years (Ansmann et al, 1993(Ansmann et al, , 2005Ansmann et al, 2009;Seifert et al, 2007Seifert et al, , 2010Seifert et al, , 2015Kanitz et al, 2011). Observations are rare in the case of liquid-water clouds because lidars are not appropriate for clouds with typical optical depths of 10 and more.…”
Section: Introductionmentioning
confidence: 95%
“…Lidars are used since the 1970s to monitor clouds and their evolution, although primarily cirrus and mixed-phase clouds (Platt, 1973(Platt, , 1977Sassen, 1991). Our group also contributed to these observations over the last 25 years (Ansmann et al, 1993(Ansmann et al, , 2005Ansmann et al, 2009;Seifert et al, 2007Seifert et al, , 2010Seifert et al, , 2015Kanitz et al, 2011). Observations are rare in the case of liquid-water clouds because lidars are not appropriate for clouds with typical optical depths of 10 and more.…”
Section: Introductionmentioning
confidence: 95%
“…Atmospheric observations indicate that heterogeneous ice nucleation in mixed-phase clouds can already occur at temperatures higher than −20 • C (Ansmann et al, 2009;Seifert et al, 2010;Kanitz et al, 2011). In contrast, laboratory studies showed that the majority of non-biological substances found in atmospheric ice crystal residues, i.e., natural mineral dust (e.g., Twohy and Poellot, 2005;Pratt et al, 2009;Kamphus et al, 2010), are only ice active at lower temperatures (e.g., Hoose and Möhler, 2012;Murray et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Based on these measurements and the Polarstern cruise data, Kanitz et al (2011) contrasted the temperature dependence of heterogeneous ice formation efficiency between the Southern Hemisphere and the Northern Hemisphere. At comparable temperatures, a much higher fraction of icecontaining clouds was found in the Northern Hemisphere, suggesting that the increased aerosol load in the northernhemispheric free troposphere is responsible for this contrast.…”
Section: Southern Hemispherementioning
confidence: 99%